The (non) paths of Rural Education in Campos dos Goytacazes: an analysis of public educational policies - Viviane Cristina Silva Lima (Universidade Estadual de Alagoas, 2021)
The history of Brazilian education shows that education projects designed for the countryside do not consider social capital and the particularities of rural territories. Thus emphasizing the arenas of power between the ruling class and the working class. In the field of educational public policies, tensions are concentrated in the discontinuities of government actions aimed at improving rural education. Brazil adopts educational plans that do not match the reality of the people of the countryside, however the public policies conquered in the last decades were an important step in the struggle for the security of working class rights.Given the above, the present research project aims to: analyze the implementation of public policies on Rural Education in themunicipality of Campos dos Goytacazes, in order to promote the development of peasant territories. For that, qualitative research was chosen as a methodological approach. Among the technical procedures adopted, bibliographic and documentary research, interviews with subjects related to Rural Education in the municipality and Caderneta de Campo, as an auxiliary tool for the systematization of data, stand out. The survey results showed that the Municipality of Campos dos Goytacazes accesses resources for theimplementation of programs aimed at Rural Education, but due to the lack of "political will", the subjects of the countryside continue to be invisible. In order to mitigate the harmful effects of the educational paradigm, it is suggested, for example, theeffective implementation of the Rural Education matrix, approved in 2016, by the municipality. The adoption of the matrix in question will contribute to the promotion of a more significant teaching-learning process for students in the field, since it places them as protagonists of the training process.